Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Akademik Siswa di Sekolah SMP Sinar Husni - Savitri, Intan; M, Marsyela; M, Marsyeli; N, Nurroyian; Nst, Abdul Fattah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of the principal's leadership style on students' academic performance at SMP Sinar Husni. The research method used is quantitative with a multiple regression approach. The population of this study was all students of SMP Sinar Husni, with samples selected by purposive sampling. Data were collected through questionnaires distributed to students regarding their perceptions of the principal's leadership style and their academic performance. Data analysis techniques used include validity, reliability, multiple regression, and t-test and R-square test. The results showed that the principal's leadership style has a significant positive effect on students' academic performance. The regression coefficient shows that every one unit increase in leadership style will increase students' academic performance by 0.487. The t-test shows a calculated t value of 9.791 which is greater than the t table (1.687) with a significance value of 0.000, indicating a significant effect. In conclusion, the principal's leadership style plays an important role in improving students' academic performance at SMP Sinar Husni.